How Do I Forestall Platelet Stockpiling? Experience from a Tertiary Care Center - Deepika Chenna; Shamee Shastry; Poornima Baliga (International Journal of Supply Chain Management, 2019)
Background:Among all the blood products, platelets had been reported to have a high rate of outdates due to its unpredictable demand and short shelf life of only 5 days. Researchers have applied techniques of management science and inventory theory to develop a model for inventory management. However, they failed to be implemented due to the variations in the demand and supply and complex computational models.Aims:To analyze the utilization pattern of platelet concentrates and discuss the method of optimal inventory management.Methods:We conducted a prospective observational study on platelet inventory practice at our center from January to December 2014. The number of units to be prepared is decided on daily basis by the transfusion medicine faculty or the resident. The utilization, wastage, expiry and the day’s cover are calculated for the study period. Future requirement is estimated based on the usage in the previous quarter, discard rare, average increase in usage and an additional 1% for managing disasters. Results:During this period a total of 6241 and 5706 units of platelet concentrates were prepared and issued respectively. The wastage rate was 5.1% and expiry rate was 3.5%. The average day’s cover of platelet units at our center was found to be 3 days using average monthly stock available and issued platelets. We observed that holding a stock of 45 units of platelets per day we had a cover for about 3 days for issue. Calculation of future requirement(6309) gave a high prediction when compared to the actual platelets prepared(6241).Conclusions:Understanding and regularly monitoring the inventory, setting up an optimum inventory level, follow of first in first out policy and to have an alternate management plan in times of shortage, like usage of apheresis products are some of the strategies which would benefit in best inventory practices.